Pelatihan Kelas Kreatif: Mengembangkan Keterampilan Seni dan Kerajinan Tangan pada Anak: Pengabdian - Dedi Gunawan; Waqiah; Titis Sri Wulan; Yayuk Chayatun Machsunah; Dita Pratama (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service program aims to develop the arts and crafts skills of elementary school-aged children in Pampang Village, Panakkukang District, Makassar City. The training program is designed to provide a creative learning experience based on a participatory, educational, and fun approach. A total of 34 children were actively involved in the three-day training, with materials including collage art, crafts based on recycled materials, and expressive drawing. The training method uses learning-by-doing techniques and daily reflection to encourage the development of children's fine motor skills, creativity, and social character. Evaluation results showed that 88% of children participated fully in the activities, and more than 91% expressed enthusiasm. Pre-test and post-test scores also showed an increase in art understanding from an average of 56 to 87. In addition, facilitators noted an increase in the children's self-confidence, initiative, cooperation, and social responsibility. The impact of this program is not only visible in the children's work, but also in changes in their attitudes and social interactions during the training. To ensure sustainability, the Pampang Children's Creative Class Community was established as a forum for continued development.